Soccer and the Postmodern Hero - Pahuacho, Alonso (2015)
The aim of this article is to reveal, through a critical analysis of the discourse,how the leading football player Paolo Guerrero has been built up in differentsporting newspaper articles as a new national hero who is able to incarnate acertain archetypical value (bravery), and introduce him as a lucky essence fromthe Peruvian national character. Through a thoughtful examination of the several discursive strategies often used by the sports press, this virtue is deconstructed in order to find the national ideology which is set up behind it. The spirit of this essay is to denature every attempt of enclosing the idea of a unique national identity in this feature, a representation which most of the sporting announcements are the responsible to show it as an irrefutable truth.